Law Enforcement For Commitment Making Officials Who Make Overpayments For Procurement of Goods/Services Without Mens Rea - Sonny Wirawan; Huala Adolf; Hernawati RAS (Fox Justi : Jurnal Ilmu Hukum, 2024)
Law enforcement in cases of criminal acts of corruption, including in the field of procurement of goods/services, must be carried out firmly and massively but measurably by prioritizing the principle of objectivity and the principles of justice and benefit. Law enforcement based on statutory regulations in the field of criminal acts of corruption should be imposed on perpetrators who truly have evil intentions (mens rea) to commit corruption. Law enforcement that does not pay attention to this aspect will result in concerns or even fear for implementing officials who make decisions, including Commitment Making Officials (PPK) in the procurement of goods/services that do not have a mens rea, that their actions could at any time be criminalized. This research aims to analyze legal enforcement for PPK who make overpayments for procurement of goods/services without mens rea and to analyze legal protection for PPK due to overpayments for procurement of goods/services without mens rea. The method used in this research is normative legal research which is carried out by examining primary legal materials as well as secondary legal materials relating to the legal issues being studied. Data was collected through document study or library research and analyzed through a qualitative approach. The research results show that law enforcement for PPK who make overpayments for procurement of goods/services can be carried out through state administrative law mechanisms or through criminal law mechanisms. The research results also show that in several cases, law enforcement based on the Corruption Crime Law was imposed on PPK who were not proven to have the mens rea to commit corruption. Legal protection for PPK due to excess payments for procurement of goods/services without mens rea has been provided by the state through a set of regulations in the field of procurement of goods/services, including as regulated in Article 84 of Presidential Regulation Number 16 of 2018 concerning Government Procurement of Goods/Services as amended by Presidential Regulation Number 12 of 2021 provides legal services to those involved in procuring goods/services in dealing with legal problems related to the procurement of goods/services provided from the investigation process to the court decision stage.